Transforming Research Excellence New Ideas from the Global South - Kraemer-Mbula, Erika; Tijssen, Robert; Wallace, Matthew L.; McClean, Robert (African Minds, 2019)
"Modern-day science is under great pressure. A potent mix of increasing expectations, limited resources, tensions between competition and cooperation, and the need for evidence-based funding is creating major change in how science is conducted and perceived. Amidst this 'perfect storm' is the allure of 'research excellence', a concept that drives decisions made by universities and funders, and defines scientists' research strategies and career trajectories. But what is 'excellent' science? And how to recognise it? After decades of inquiry and debate there is still no satisfactory answer. Are we asking the wrong question? Is reality more complex, and 'excellence in science' more elusive, than many are willing to admit? And how should excellence be defined in different parts of the world, particularly in lower-income countries of the 'Global South' where science is expected to contribute to pressing development issues, despite often scarce resources? Many wonder whether the Global South is importing, with or without consenting, the flawed tools for research evaluation from North America and Europe that are not fit for purpose. This book takes a critical view of these issues, touching on conceptual issues and practical problems that inevitably emerge when 'excellence' is at the center of science systems. Emerging from the capacity-building work of the Science Granting Councils Initiative in sub-Saharan Africa, it speaks to scholars, as well as to managers and funders of research around the world. Confronting sticky problems and uncomfortable truths, the chapters contain insights and recommendations that point towards new solutions - both for the Global South and the Global North."